2015
DOI: 10.3332/ecancer.2015.594
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell carcinoma of the head and neck region: treatment and outcomes of 15 patients

Abstract: IntroductionSpindle cell carcinoma of the head and neck is a rare entity and the evidence of optimal management is lacking. The objective of our study was to report the treatment and outcomes of 15 patients treated in a single institution over a seven year period.Materials and MethodsA total of 15 patients (12 males and 3 females) with spindle cell carcinoma of the head and neck were treated between July 2007 to June 2014. In six patients the disease developed after previous radiotherapy. Of the 15 patients, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
(25 reference statements)
0
28
0
Order By: Relevance
“…Either radiotherapy or chemotherapy is an alternative option for inoperable patients or those with sinonasal tumors. Overall, the time of diagnosis and the site of lesion affect the outcome so that early stage diagnosis and extraoral lesion have been resulted in better outcomes (12)(13)(14)). Some studies reported the increased mortality rate in the tumors of the head and neck area as a result of lower resistance to tumor-spreading along tissue planes and extensive lymph drainage system with resultant lymphatic and distant metastases (3,4,13).…”
Section: Discussionmentioning
confidence: 99%
“…Either radiotherapy or chemotherapy is an alternative option for inoperable patients or those with sinonasal tumors. Overall, the time of diagnosis and the site of lesion affect the outcome so that early stage diagnosis and extraoral lesion have been resulted in better outcomes (12)(13)(14)). Some studies reported the increased mortality rate in the tumors of the head and neck area as a result of lower resistance to tumor-spreading along tissue planes and extensive lymph drainage system with resultant lymphatic and distant metastases (3,4,13).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies [4,15,16] suggested that the patients who underwent operation had a more favorable outcome. Some observational studies [4,16] showed a less favorable outcome in patients who received radiotherapy alone compared with the operation group, while the authors of the study admitted that selective bias should be considered, as the patient who was not feasible for surgery probably represented the more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…The rule of adjuvant chemo or radiotherapy still remains unclear. A series with 15 cases [15] was an overview of treatment of SpCC, in which surgery with adjuvant radiotherapy or chemotherapy seemed to reduce the recurrence rate of tumor. As a result, operation as the first line therapy whenever the tumor is resectable, following adjuvant chemo or radiotherapy, may reach a more favorable outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No definite treatment protocol exists for this unique entity and tumour is primarily treated with aggressive, wide local excision. Adjuvant radiation and/or chemotherapy should be used in case of incomplete removal or positive surgical margins [12]. While other studies suggest that postoperative chemoradiation therapy improves patient prognosis and should be considered as the standard therapeutic modality [13].…”
Section: Carcinosarcomasmentioning
confidence: 99%